Challenges Facing the Wood Trade in Europe - Ioana Claudia Dobre (Ovidius University Annals: Economic Sciences Series)
In this study we will focus on the analysis of the wood trade at global, European and national level (Romania), in order to identify both the demand and supply, as well as the challenges facing this market. Sustainable management of forest resources is essential to ensure a continued and beneficial role of wood in economic development. Further action is needed at European and governmental level to support producers and ensure a balance between economic needs and the sustainable conservation of forest resources on the European continent.